Antibiotic-loaded bone cement and its widespread use: is it justified? - Calonego, Giovanni (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Along with a steady rise in the volume of joint prostheses implanted every year worldwide, there has been a rise in revision after total hip arthroplasty (THA) and total knee arthroplasty. Among the main reason for THA revision, infection accounts for 12.0–25.2 %. Nowadays the use of antibiotic-loaded bone cement (ALC) with the aim to reduce periprosthetic joint infection (PJI) has greatly increased. The use of ALC in primary prosthesis fixation is still debated. So in order to be able to provide a reasonable and scientific answer to this question one should first analyze data from scientific literature. In terms of prophylaxis, it was demonstrated in many investigations that the combined use of systemic antibiotic and ALC in THA was producing the lowest risk of revision due to infection. The release of antibiotic from ALC has a well known kinetics, with a peak release during the first days followed by a long tail of lower release. The choice of adding an Aminoglycoside (Gentamicin) was based on release studies which demonstrated that among antibiotics Gentamicin was showing the best elution performances from the bone cement, the most extended spectrum of activity and no negative effects on mechanical performances. As regards possible problems associated with the presence of antibiotic in bone cement the following should be considered: systemic toxicity, hypersensitivity reaction, mechanical hazards, bacterial resistance hazards and cost rising. In conclusion, the use of ALC must be considered as a support strategy in prevention and not the solution of infections; in primary implants, ALC is justified only in high risk patients; it is recommended for revisions; the perfect antibiotic in ALC does not exist; avoid using Vancomycin as first step; ALC is successful only if associated with systemic antibiotics.